A Python Package for Heart Rate Variability Analysis and Signal Preprocessing. (6th October 2021) - Champseix, Robin; Ribiere, Laurent; Le Couedic, Clément
This paper presents hrv-analysis, a Python package for Heart Rate Variability (HRV) analysis. hrv-analysis is an open-source package for the Python statistical computing environment, which supports a wide variety of time, frequency and non-linear HRV analysis methods. It also includes several functions for signal preprocessing like outliers and ectopic beat removal. This package is suitable for researchers, professionals working in healthcare as well as for developers and more widely for anyone willing to perform detailed analysis on heart rate variability. hrv-analysis was developed as part of the Aura project. Aura is a non-profit project aiming to develop an open-source forecasting system to help people suffering from epilepsy regain autonomy in their everyday lives. This package was developed using Python 3.